Glomus tumor in the abdominal wall - Kelen Chistina A. Bezzerra; Djulienne Marly K. Reis; Franciele Carla Prichoa
ABSTRACT The glomus tumor is a rare benign soft tissue tumor. We report a case of a 45-year-old male patient who presented with a painful mass in the abdominal wall. The patient underwent total tumor resection and the anatomical pathology diagnosis was of glomus tumor. The glomus tumor presents differential diagnosis of carcinoid tumor, hemangiopericytoma and vascular leiomyoma.